Probabilistic risk assessment of dietary exposure to pentachlorophenol in Guangzhou, China. Issue 2 (1st February 2023) - Zhang, Yuhua; Mhungu, Florence; Zhang, Weiwei; Wang, Yanyan; Li, Hailin; Liu, Yufei; Li, Yan; Gan, Pingsheng; Pan, Xinhong; Huang, Jie; Zhong, Xianwu; Song, Shaofang; et al.
Abstract: Pentachlorophenol (PCP) is a ubiquitous environmental contaminant commonly existing as its sodium salt (NaPCP), which enters the human body primarily through long term but low-level dietary exposure. PCP contributes to chemical carcinogenesis and teratogenesis. In this study, the probabilistic risk of dietary exposure to PCP in Guangzhou citizens was investigated. In total, 923 food samples in the categories of pork, livestock (beef and lamb), poultry, offal, eggs, and freshwater fish (considered to be relatively susceptible to PCP contamination) were collected from various markets in Guangzhou and tested for PCP. Probabilistic risk assessment model calculations for PCP dietary exposure and margin of exposure (MOE) values were performed using @RISK software, based on a Monte Carlo simulation with 10, 000 iterations. The overall detection rate of PCP (above 1 μg kg −1, the detection limit) was 19.9% (184/923), with an average of 7.9 μg kg −1 . The highest rate of PCP detection, 28.2%, was in livestock (beef and lamb). The MOE value for dietary PCP exposure in general Guangzhou residents averaged 400, which was far below 5, 000 (the borderline for judging a health risk). The lowest MOE value, 190, was observed in the 3- to-6-year old population and indicates a significant risk. In conclusion, this study suggests that PCP exposure in Guangzhou residents is of considerable health risk, especially for the pre-school young children.